If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -11 = -6 + 16 Reorder the terms: -11 + 3x = -6 + 16 Combine like terms: -6 + 16 = 10 -11 + 3x = 10 Solving -11 + 3x = 10 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '11' to each side of the equation. -11 + 11 + 3x = 10 + 11 Combine like terms: -11 + 11 = 0 0 + 3x = 10 + 11 3x = 10 + 11 Combine like terms: 10 + 11 = 21 3x = 21 Divide each side by '3'. x = 7 Simplifying x = 7
| 9x^2+37x-46=0 | | 9(-7)-3y=-63 | | 9x-3y=-63 | | 24(b-1)+21=3(8b-1) | | 40+4y-16=-13y-12-3y | | 3y-2x=30 | | 3(n-6)=2n | | 6y+5x=30 | | 5x-6y=-35 | | 4x+3y=-28 | | 2+3x=13+x | | 5x-1=14-100 | | 19+3x=14+2x | | 6x+18=16x-32 | | 51+6y-18=17y-12-2y | | 7x-26=37 | | 8-10[4-(-2+18)3]= | | (2x+3)(3x-5)= | | (2x^2y^2-3xy+4)(4xy^2)= | | (2x-1)(x-5)(x-8)=0 | | 2ab+a+5ab+b= | | x^2+35x+19= | | 9-x=1+x+18 | | x=2x-4 | | 78-4x=14x+20 | | 9-9x=41-23x | | 3x+6=62-4x | | 5x+23=13x-73 | | 7x-28=49 | | 4(x-2)=x+5(x-4) | | 3x^2-2x-133=0 | | -2-3x=3-x |